МЕТОД РОЗРАХУНКУ ЕЛЕКТРОМАГНІТНОГО ПОЛЯ СПІРАЛЕПОДІБНОЇ ІНДУКЦІЙНОЇ СИСТЕМИ ДЛЯ МАНІТОІМПУЛЬСНОГО ОБРОБЛЕННЯ НЕМАГНІТНИХ МЕТАЛЕВИХ СМУГ З ФЕРОМАГНІТНИМ ЕКРАНОМ - Ращепкін, А.П.; Кондратенко, І.П.; Карлов, О.М.; Крищук, Р.С. (Інститут електродинаміки НАН України, Київ, 2022)
Pulsed currents and magnetic forces of an induction system with a spiral winding and a ferromagnetic shield for processing non-magnetic thin-sheet metal strips in order to create magnetoplastic, electroplastic effects due to eddy currents are studied. Under the strip there is the ferromagnetic shield, and above it – spiral winding. The aim of the work is to develop an analytical method for calculating transients of pulsed currents in an electric circuit with the induction system and a capacitor charged to certain voltage taking into account influence of the ferromagnetic shield to perform investigation of time-varying magnetic field. Electromagnetic parameters of the inductor are determined by computer simulation using the finite element method in the mode of harmonic currents. Current transients in the electric circuit are calculated using known in theoretical electrical engineering mathematical dependences and distribution of current density and magnetic forces in the strip is calculated by the finite element method in the mode of transients. Influence of the ferromagnetic shield on electromagnetic processes in the induction system for the set ranges of strip’s thickness, its electrical conductivity and current frequency is established. Electromagnetic force between the spiral winding and the strip, the current density in the strip, as well as the moments of time at which the current and force have maximum values are studied. References 14, figures 6, tables 2.